Systematic position of Thraulodes Ulmer 1920 (Ephemeroptera: Leptophlebiidae) and descriptions of new and little-known species - Kluge, Nikita J. (Zootaxa, 2020)
The general characteristics of Thraulodes given by Traver and Edmunds (1967), is supplemented by the following: Larval labrum not always lacks median emargination, but in certain species the emargination is exposed ventrally and invisible from dorsal view; 5 denticles separated by 6 sensilla on its distal margin are initial for Ephemeroptera and present in all examined species of Thraulodes. Horseshoe row of hairs on dorsal side of glossa is characteristic for Thraulodes. Setal rows on larval femora and tibiae of fore, middle and hind legs are constant and peculiar for Thraulodes, while size and shape of the setae forming these rows is species-specific. The pair of «spears» on apices of penes represent rolls, whose canal serves as continuation of seminal duct; in course of genital development in last-instar larva, these spear-like rolls appear in the same way as tubular telopenes of Hermanellonota, that testifies about their homology. Based on this synapomorphy, Hermanellonota and Thraulodes are united into the new taxon Hermanellandria taxon n. New terms for describing coloration of subimaginal mesonotum are suggested. The following species and stages of development are described: (1) larva, subimago and ♂ imago of Th. ludmilae sp. n. from Panama; (2) larva, subimago, ♂ & ♀ imago and egg of Th. sinuosus Mariano & Flowers 2011 from Panama; (3) larva, subimago, ♂ & ♀ imago and egg of Th. telegraphicus Needham & Murphy 1924 from Peru; (4) larva, subimago, ♂ & ♀ imago and egg of Th. panamensis sp. n. from Panama; (5) subimago, ♂ & ♀ imago and assumed larva of Th. viviparus sp. n. from Panama; (6) larva, subimago, ♂ & ♀ imago and egg of Th. schlingeri Traver & Edmunds 1967 from Peru; (7) larva, subimago, ♂ & ♀ imago and egg of Th. marreroi Chacon et al. 1999 from Panama; (8) larva, subimago, ♂ & ♀ imago and egg of Th. quevedoensis Flowers 2009 from Peru; (9) larva, subimago, ♂ & ♀ imago and egg of Th. fascipennis sp. n. from Panama; (10) larva, subimago, ♀ imago and egg of Th. zonalis Traver & Edmunds 1967 from Panama; (11) larva, subimago, ♂ & ♀ imago and egg of Th. flavus sp. n. from Panama; (12) larva, subimago, ♂ & ♀ imago and egg of Th. spangleri Traver & Edmunds 1967 from Panama; (13) larva, subimago, ♂ & ♀ imago and egg of Th. niger sp. n. from Peru; (14) subimago, ♂ imago and assumed larva of Th. nigrabdominalis sp. n. from Peru; (15) larva, subimago, ♂ & ♀ imago and egg of Th. nigripes sp. n. from Peru; (16) larva, subimago, ♂ & ♀ imago and egg of Th. nigrotibialis sp. n. from Peru; (17) larva, subimago, ♂ & ♀ imago and egg of Th. alboniger sp. n. from Peru; (18) larva and subimago of Th. lepidus (Eaton 1884) from Panama. Unassociated larvae under arbitrary names Thraulodes sp. «Palo Seco» and Thraulodes sp. «Itaya» are described from Panama and Peru correspondingly. Additional descriptions of larva and subimago presumably determined as Th. consortis Domínguez 1987 are given. These species are arranged into several species groups, some of which are arbitrary, and some natural, e.g., the natural group sinuosus comprising Th. sinuosus and Th. ludmilae and the natural group schlingeri comprising Th. schlingeri and Th. marreroi. Th. cryptodrylus Nieto & Dominguez 2001 is a valid species name, not a synonym of Th. lepidus. Probable ovoviviparity is reported for Th. viviparus sp. n.